Sirt1 Suppresses Burn Injury-Induced Inflammatory Response through Activating Autophagy in Raw264.7 Macrophages. (March 2021) - Han, Fu; Li, Zhenzhen; Han, Shichao; Jia, Yanhui; Bai, Lu; Li, Xiaoqiang; Hu, Dahai
The present study sought to investigate the association between silent information regulator 1 (SIRT1) and autophagy during systemic inflammatory response syndrome following burn injury. The experimental burn model in mice and macrophages were established. SIRT1 mRNA expression was quantified by quantitative real-time PCR. The protein levels of SIRT1 and the conversion of light chain 3 (LC3)-I to LC3-II were determined by western blot analysis. The formation of autophagosomes was assessed by green fluorescence protein-tagged LC3 fluorescence. The contents of inflammatory cytokines interleukin (IL)-1, IL-6, IL-10 and IL-18 were measured by ELISA. SIRT1 was highly expressed in burned tissues and RAW264.7 cells treated with serum obtained from mice with burn injuries. Moreover, SIRT1 overexpression augmented, whereas sirtinol, an inhibitor of SIRT1, attenuated burn injury-induced increasing number of autophagosomes and expression levels of LC3-II/LC3-I in RAW264.7 cells. Besides, sirtinol effectively prevented SIRT1-induced pro-inflammation during burn injury. Furthermore, autophagy inhibition by 3-methyladenine significantly attenuated SIRT1 overexpression-mediated pro-inflammatory cytokine production. SIRT1 abolished burn injury-induced inflammatory response by inducing autophagy.